Pengaruh Pendidikan Kesehatan terhadap Kepatuhan Konsumsi Tablet Fe pada Ibu Hamil: Literature Review - Ezi Emira; Anggi Dheana Karin; Nur Afni; Lina Handayani (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: The incidence of anemia in pregnant women has reached 48.9%. Some of the factors that cause anemia include poor adherence to Fe tablet consumption, mainly due to the low knowledge and attitudes of pregnant women regarding the importance of consuming Fe tablets during pregnancy. This systematic review aims to determine the effect of health education on pregnant women on adherence to consuming Fe tablets. Methods: Using an in-depth content analysis method on selected articles using the keywords “Compliance, Iron Supplements, pregnant women, health education” in the PUBMED and ProQuest databases. Articles are selected in stages using the PRISMA Appraisal Tool. Results: From 438 articles, finally 5 articles were obtained. From the five final articles, it was found that there was an effect of health education on the knowledge and attitudes of pregnant women about Fe tablets and that there was an effect of health education on the compliance of pregnant women in consuming Fe tablets. Conclusion: Health education for pregnant women is very influential on adherence to Fe tablet consumption, although if it is done with low intensity it has little effect. This finding is important for health educators to focus on updating strategies and developing health education practices to increase knowledge and compliance of pregnant women in consuming Fe tablets.